Menggali Peran Distribusi dan Promosi dalam Menciptakan Pelanggan Setia: Studi Kasus pada PT Kongruen Medika Nasional - Putu Padmidewi Wijaya Kusuma; Luh Gede Elvina Adi Saputri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Current study aims to investigate the role of distribution channels and promotional activities in increasing customer satisfaction and creating customer loyalty. This study was conducted at PT Kongruen Medika Nasional targeting the population, namely all customers of PT Kongruen Medika Nasional as many as 268 outlet leaders. Through the simple random sampling method and sample calculation, 75 outlet leaders were obtained as respondents. Empirical data were collected through a 10-point Likert scale questionnaire and analyzed using the PLS-SEM approach. The study findings prove that customer satisfaction can be created through a good distribution system and properly implemented promotional activities. Furthermore, high loyalty can also be created through a good distribution system, good promotional activities, and high satisfaction. An interesting finding in this study is that customer satisfaction is proven to be able to act as a mediating construct between the relationship distribution to loyalty and the promotion of loyalty. This study is able to make a positive contribution to the literature and for PT Kongruen Medika Nasional in increasing customer loyalty and satisfaction through determining the right distribution channels and implementing good promotions.